Homeschooling reframed narratives of Filipino mothers of learners with disabilities - Tan Pascual, Anna-Liza Y.
The purpose of this study was to describe how Filipino families homeschool their learners with disabilities (LWD). This study sought to determine what contributed to the decision of Filipino families to go into and remain in homeschooling (HS) their LWD and what are the outcomes of their decisions in HS their LWD. Informed by theoretical perspectives on push-pull and agency, a qualitative research design using a narrative inquiry approach was used. Eight Filipino mothers who homeschool their children were recruited through random sampling. Data was collected using a demographic questionnaire, interviews, and audio-visual materials. Data was analyzed using the data analysis spiral to develop the thematic model. Findings derived include: (1) There are factors that push families into HS, and there are factors that pull them to stay. (2) There are enablers and disablers that influence families while they are HS. (3) Parental agency is achieved in the course of HS. Findings unique to this study were the view of HS parents about family, the value they place on working with a team of professionals, and the educational management skills that parents learn as they homeschool their children. As a contribution to the field of Special Education, this study has formulated a conceptual framework for HS LWD among Filipino families.